(untitled) (The Review of Diabetic Studies, 2025)
Diabetic neuropathy, a prevalent complication of diabetes mellitus affecting up to 50% of patients worldwide, manifests as peripheral nerve damage leading to debilitating pain, numbness, and reduced quality of life. Hyperglycemia-induced oxidative stress and inflammation play central roles in its pathophysiology, exacerbating nerve dysfunction through free radical generation, mitochondrial impairment, and cytokine release. Current treatments, including antidepressants (e.g., duloxetine), gabapentinoids, and SNRIs, offer limited efficacy (relief in only 30% of cases), with challenges such as adverse effects (e.g., somnolence, gastrointestinal issues) and poor adherence. This review explores the ameliorative potential of antioxidants, particularly vitamins C and E, in mitigating diabetic neuropathic pain (DNP). These agents neutralize reactive oxygen species, restore antioxidant defenses (e.g., glutathione regeneration), and modulate molecular pathways like NMDA receptor activity and PKC activation, thereby reducing inflammation and improving nerve conduction. Preclinical and clinical evidence, including randomized trials showing enhanced pain scores (e.g., VAS reductions) and quality-of-life improvements with vitamin C (200 mg/day) plus duloxetine or vitamin E (400–700 mg/day) supplementation, supports their adjunctive role. Synergistic effects of combined C and E vitamins further enhance neurotrophic support and glycemic control. Despite promising outcomes, long-term studies are needed to optimize dosing and integration with standard therapies. Antioxidants represent a cost-effective, safe strategy to address DNP’s unmet needs, warranting inclusion in clinical guidelines.